2007
DOI: 10.1007/s10157-007-0484-5
|View full text |Cite
|
Sign up to set email alerts
|

The characteristics of relapse in adult-onset minimal-change nephrotic syndrome

Abstract: To develop effective therapeutic modalities, it is important to have a thorough understanding of the clinico-pathophysiological characteristics of MCNS patients showing relapse.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
25
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 30 publications
(25 citation statements)
references
References 19 publications
0
25
0
Order By: Relevance
“…Although few patients with MCD progress to ESRD, a series of studies reported that approximately 30%-70%, most commonly 60%, of adult MCD patients experienced at least one relapse of proteinuria (7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18) and that 50%-60% of patients with a first relapse subsequently experienced a second relapse (7)(8)(9)(10)(11)(12). Thus, clinical goals in MCD patients are early induction of remission of proteinuria and more importantly, prevention of relapse of proteinuria.…”
Section: Introductionmentioning
confidence: 99%
“…Although few patients with MCD progress to ESRD, a series of studies reported that approximately 30%-70%, most commonly 60%, of adult MCD patients experienced at least one relapse of proteinuria (7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18) and that 50%-60% of patients with a first relapse subsequently experienced a second relapse (7)(8)(9)(10)(11)(12). Thus, clinical goals in MCD patients are early induction of remission of proteinuria and more importantly, prevention of relapse of proteinuria.…”
Section: Introductionmentioning
confidence: 99%
“…4,8 Most studies, in fact, 5,6,8,9,18,21,22 have reported higher IgE levels in MCD patients compared to the control group. Fuke et al 6 have shown that high IgE levels in nephrotic relapse, instead of playing a direct role in pathogenesis, are in fact a result of a dysfunction of the humoral immune system.…”
Section: Discussionmentioning
confidence: 99%
“…Increased IL-13 levels have been found in children with MCD in relapse when compared with remission and control group. 6,15,[21][22][23] Although the IL-13 secreted from the T-cell was found to be directly associated with IgE, studies on IL-4 revealed different results. 18,[24][25][26][27][28] Podocytes express the CD80 receptor for IL-13 binding.…”
Section: Discussionmentioning
confidence: 99%
“…Increase of the cumulative dose of prednisolone was dependent on the occurrence of relapse. In our previous study, the relapse group showed a significantly higher incidence of corticosteroid side effects, such as osteoporosis (37). The BMD at the baseline was significantly high, and the urinary NTx and serum ALP levels at the baseline tended to be high as compared with that at the 12-month observation.…”
Section: Discussionmentioning
confidence: 99%